Variance utilization as an alternative methodology for integrating genetic maps - Salgado, Caio Césio; Cruz, Cosme Damião; Nascimento, Moysés; Barrera, Carlos Felipe Sanches (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this work was to develop an integration process of genetic maps using the inverse variance, and to test its efficiency. Simulated F2 codominant populations and backcrosses of 100, 150, 200, and 400 plants were used, considering a virtual diploid species with 2n = 2x = 2 chromosomes, with total genome length per linkage group estipulated in 100 cM, 21 marks per linkage group, and equidistant markers spaced at 5 cM. The genomes were compared for linkage group size, distance variance between adjacent marks, Spearman correlation and stress related to the estimated distances adequation. Each simulated genome was fragmented into four new maps: three with eight makers and one with nine, each containing four anchor markers. The maps were aligned, ordered, integrated and, then, compared with the original map. The proposed map integration process proved to be effective. The generated maps showed a little internal tension in comparison to the original ones. Map integration depends on the population type, population size, marker type, recombination frequency, and on the linkage phase.
Keywords: recombination frequency; linkage groups; molecular marker; internal tension